2022
DOI: 10.1016/j.crphar.2021.100079
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sialylation and fucosylation of saliva glycoproteins: Characteristics of lung cancer-specific biomarkers

Abstract: Dysregulated surface glycoproteins play an important role in tumor cell proliferation and progression. Abnormal glycosylation of these glycoproteins may activate tumor signal transduction and lead to tumor development. The tumor microenvironment alters its molecular composition, some of which regulate protein glycosylation biosynthesis. The glycosylation of saliva proteins in lung cancer patients is different from healthy controls, in which the glycans of cancer patients are highly sialylated and hyperfucosyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 140 publications
(174 reference statements)
0
16
0
Order By: Relevance
“…Numerous reviews have been published describing potential novel biomarkers for LC identified by proteomics studies, such as GRIP and coiled-coil domain-containing protein 2 (GCC2), Cystatin A, macrophage migration inhibitory factor (MIF), Thymosin β4, and Fascin [ 9 , 10 ]. Most potential blood [ 11 , 12 , 13 ] and saliva [ 14 ] markers identified for early diagnosis have not been implemented in clinical practice yet. The analysis of fresh-frozen or formalin-fixed paraffin-embedded (FFPE) tissue specimens/sections provides the basis of cancer research; several studies have been published previously about the proteomic characterization of NSCLC tissue [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reviews have been published describing potential novel biomarkers for LC identified by proteomics studies, such as GRIP and coiled-coil domain-containing protein 2 (GCC2), Cystatin A, macrophage migration inhibitory factor (MIF), Thymosin β4, and Fascin [ 9 , 10 ]. Most potential blood [ 11 , 12 , 13 ] and saliva [ 14 ] markers identified for early diagnosis have not been implemented in clinical practice yet. The analysis of fresh-frozen or formalin-fixed paraffin-embedded (FFPE) tissue specimens/sections provides the basis of cancer research; several studies have been published previously about the proteomic characterization of NSCLC tissue [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our proteomic study, we used the SPECS method to enrich the secreted glycosylated proteins for their identification because glycosylated proteins play important roles in cancer development and progression . However, during the biochemical validation, in order to prevent the interference of FBS with immunoblotting, we used a medium without FBS to culture cells and immunoblotted the cultured medium after concentrating.…”
Section: Discussionmentioning
confidence: 99%
“…In our proteomic study, we used the SPECS method to enrich the secreted glycosylated proteins for their identification because glycosylated proteins play important roles in cancer development and progression. 51 However, during the biochemical validation, in order to prevent the interference of FBS with immunoblotting, we used a medium without FBS to culture cells and immunoblotted the cultured medium after concentrating. Although our experiments revealed the similar upregulation of CD146 in these two cases, we are not sure whether other proteins exhibit similar or different behaviors under two different culture conditions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Protein glycosylation is inherently related to the physiological state of cells, and its abnormal regulation manifests the occurrence and development of diseases. This is partly due to the differential expression and availability of GTFs or GSs in the disease microenvironment [6, 7]. OGA (O‐GlcNAcase) and OGT dynamically regulate Ser/Thr O‐GlcNAcylation in diseases [8].…”
Section: Diverse Biological Roles Of Glycosylation In Health and Diseasementioning
confidence: 99%